Non-healing wound suspicious of foreign body - Kshetri, Samir; Ghimire, Rajan; Thapaliya, Saroj; Shrestha, Nawaraj; Shrestha, Paras (Journal of General Practice and Emergency Medicine of Nepal, 2023)
A 55-year-old male, known case of type II diabetes mellitus, from Manthali – 1, Ramechhap presented with history of fall injury from tree one day back followed by pain and swelling over his right face. He presented with history of swelling over right cheek extending from right chin to right forehead. Despite of many counselling, patient refused to visit higher center for further management. He was under oral antibiotics, oral hypoglycemic agents. On subsequent follow up, we noticed pus drainage near from right medial canthus. After one month of incident, Incision and drainage was done and black chunk of wooden piece (5x2cm) were removed.